Strengthening Teachers’ Digital Media Competence: A Community-Based Training on Powtoon for Mathematics Educators in Tanjung Jabung Barat - Winarni, Sri; Kumalasari, Ade; Rohati, Rohati; Marlina, Marlina; Junita, Ranisa; Nusantara, Duano Sapta (Jurnal Karya Abdi Masyarakat, 2025)
This community-based training initiative aims to enhance the digital media competencies of mathematics teachers using Powtoon for developing engaging educational content. The program was implemented in sequential phases: planning, action, observation and evaluation, and reflection. During the planning phase, coordination was established with partner schools and core implementation teams were formed. The training program was then introduced and collaboratively scheduled with the participants. In the action phase, teachers participated in hands-on workshops focused on designing instructional media using the Powtoon application. Observations during the implementation showed active teacher engagement and progressive skill acquisition. The evaluation and reflection phases highlighted the program’s effectiveness and areas for improvement. Follow-up mentoring ensured sustainability by guiding teachers in independently producing animated learning content. Conducted at Senior High School Number 2 Tanjung Jabung Barat—home to the senior high school mathematics teacher’s association (MGMP in Bahasa)—this program successfully enabled senior high school mathematics teachers to integrate Powtoon into their instructional practices. The training not only fostered digital creativity but also promoted collaborative professional development. This initiative demonstrates a scalable model for empowering educators in rural areas with relevant digital tools to enhance teaching quality.